Functionality of an Air Duct Model as a Teaching Aid - Yunus, Faizal Amin Nur; Noor Farahanis Zaima Othman (Research and Innovation in Technical and Vocational Education and Training, 2025)
There are some issues such as the lack of facilities in terms of the existing ABBM that does not focus on the installation process because it is only for taking readings or data. Students are only focused on the diagnosis process and not on the installation process. Also, not knowing whether the incoming and outgoing airflow is correct or not CFM which has been set where the existing ABBM does not have a damper. This study is the development of an Air Duct Model as ABBM for subjects at the FPTV Refrigeration and Air Conditioning Workshop. This ABBM model has been developed based on the ADDIE model and helps the teaching and learning process in terms of theory and practice where existing facilities are lacking. The researcher has obtained confirmation from three experts who have experience in the field of Refrigeration and Air Conditioning. The results of this study show that the model produced has a design that is suitable for use and can function well and there are improvements as ABBM. This ABBM model is a learning model for students that can increase a high level of understanding and give a real picture and it is very suitable to be used by lecturers as a teaching medium during PdP sessions.